Role of dual source multidetector row cardiac computed tomography angiography in diagnosis and management of congenital heart disease patients - Chaosuwannakit, Narumol (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2017)
Introduction : Primary evaluation of patients with congenital heart disease (CHD) traditionally relies on echocardiography and conventional cardiac angiography (CCA), both of which have potential limitations. Aim : To test the hypothesis that cardiac computed tomography angiography (CCTA) is useful in the diagnosis and management of these patients. Material and methods : The 3-year observational, analytical, retrospective, cohort study included a total of 111 tomographic studies of patients with congenital heart disease. Computed tomography scans were read twice and medical records were reviewed. The Aristotle complexity was assessed as well as and the contribution of new data in relation to clinical suspicion and diagnostic change was evaluated by two expert readers who were blinded for clinical outcome in consensus reading. The confidence interval was set at 95% and a p-value of < 0.05 was used as the cutoff for statistical significance. Results : In total, 111 patients were included (56 men and 55 women) with a mean age of 7.2 years (1 day–71 years). The therapeutic procedure was performed without additional tests in 85.8% of patients. New findings were observed in 60.4% of patients and a subsequent change in management in 46.9%. New unexpected findings in CCTA prompted changes in management in 86.8% of patients. There were no significant differences in age between patients with new findings vs. patients without such findings in CCTA suggesting that CCTA-supported diagnosis of CHD is independent of age. Conclusions : Use of dual-source cardiac computed tomography yields good diagnostic performance in congenital heart disease, prompts changes in management in more than one-third of patients, and reveals new findings in relation to the presumed diagnosis in most patients.